Anaerobic peak power, fatigue index and anaerobic capacity of menstrual phases among sedentary colleciate / Fatin Farlina Marzuki - Marzuki, Fatin Farlina (Faculty of Sports Science and Recreation, 2018)
The menstrual cycle releases various types of hormones in maintaining homeostasis and organizes female reproductive system for conception every 23-28 days. The hormones that are secreted will act differently on the body. Thus, the study was conducted to investigate anaerobic peak power, fatigue index and anaerobic capacity on menstrual phases among sedentary collegiate. Wingate testing (WAnT) protocol have been set to measure peak power, fatigue index and anaerobic capacity on different phases. One-way repeated measure ANOVA was used to identify the mean and standard deviation of each phases according the parameter had been set up at earlier of the study. The result show that there was no significant different on anaerobic peak power, fatigue index and anaerobic capacity at menses, follicular and luteal phase of endometrial menstrual cycle. As for conclusion, hormone alterations during phases of endometrial menstrual cycle did not give affect towards anaerobic performance